Exploration of Dance Choreography Course in Colleges and Universities in the Context of Curriculum Civics - Yang, Wenjia (Journal of Research in Vocational Education, 2025)
With the full integration of the curriculum civics education concept into the college teaching system, as an important part of art education, the dance choreography course is faced with the urgent need for the innovation of teaching concepts, the optimization of teaching content, and the innovation of teaching methods. This paper focuses on the teaching of college dance choreography courses in the context of curriculum civics, analyzes the necessity of integrating curriculum civics into dance choreography teaching, points out the problems existing in the teaching of college dance choreography courses, and discusses the innovative strategies for integrating curriculum civics into college dance choreography teaching from the aspects of teaching concepts, teaching content, teaching methods, and evaluation systems. It aims to provide theoretical references and practical guidance for cultivating dance choreography talents with both professional skills and noble ideological and moral qualities, and promote the organic unity of educational objectives and educational functions of dance choreography courses in the new era.